The probable genetic introgression between Walia ibex (Capra walie) and domestic goats (Capra hircus) at simien mountains national park (SMNP) in Ethiopia - Alemayehu, K.; Gizaw, Solomon; Mekasha, Yoseph; Haile, Aynalem; Dessie, Tadelle (2011)
An exploratory survey was conducted at Simien mountains national park (SMNP) and bordering districts to assess the genetic introgressions between walia ibex (C. walie) and domestic goats (Capra hircus) in Ethiopia by studying breeding strategies, production and grazing systems. About 96.9% of the farmers practiced extensive goat production system. The common goat grazing places include outside and within SMNP with an index value of 0.60 and 0.36 respectively. Does selected with selection preferences of size, twining and mothering ability with an index of 0.28, 0.15 and 0.14 but, size, libido and growth was preferred for bucks with an index value of 0.35, 0.13 and 0.11 respectively. Relationships among indices with highest value traits were correlated. The correlation of size with pedigree was significant in both females and males (p < 0.01). This indicated farmers' interest to interbreeding their goats with the Walia to get strong and huge hybrid. The traits between C. hircus and C. walie (r = 0.38, p > 0.05) as well as C. walie and the suspected hybrid goat (r = 0.21, P > 0.05) were negatively correlated. However, traits between the suspected hybrid and C. hircus were positively correlated (r = 0.34, p < 0.05). Therefore, there is trepidation of introgressive hybridization between C. hircus and C. walie. However, there were no persuasive evidences that shown interbreeding between the two species.